Coronary microvascular dysfunction in post-PCI target vessels: a systematic review and meta-analysis of prevalence and associated outcomes - Li, Yunze; Duan, Jinlan; Liu, Hongxu; Lin, Sheng; Xu, Hongkun; Li, Xiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary microvascular dysfunction (CMD) in post-percutaneous coronary intervention (PCI) target vessels is increasingly recognized as a critical determinant of adverse cardiovascular outcomes, yet its prevalence and prognostic implications remain poorly characterized. We conducted a systematic review and meta-analysis to determine the prevalence of CMD in post-PCI target vessels and its associated clinical outcomes.MethodsWe conducted a systematic review and meta-analysis of observational studies using quantitative coronary physiological assessments to evaluate CMD in post-PCI target vessels. Databases (PubMed, Embase, Web of Science) were searched from inception to January 2025. The pooled Prevalence, multivariable-adjusted hazard ratio (HR) and 95% confidence interval (CI) for clinical outcomes were calculated using random-effects models.ResultsA total of 21 observational studies involving 6,632 patients were included. The pooled prevalence of CMD in post-PCI target vessels was 41.66% (95% CI: 34.18%–49.34%). Subgroup analyses revealed numerical variations in CMD prevalence across assessment methods, sex, clinical diagnoses, and target vessels, though intergroup differences did not reach statistical significance (all P > 0.05). The pooled prevalence of CMD was numerically higher in females (46.22% vs. 36.73% in males), patients with acute coronary syndrome (42.37% vs. 36.04% in chronic coronary syndrome), and those assessed via non-wire-based methods (44.72% vs. 35.65% in wire-based methods). CMD prevalence was comparable across target vessels (left anterior descending artery: 37.34%, left circumflex artery: 38.50%, right coronary artery: 39.09%). Patients with post-PCI thrombolysis in myocardial infarction (TIMI) flow grade ≤2 exhibited higher CMD prevalence than those with TIMI flow grade 3, with a statistically significant difference (75.36% vs. 37.26%, P = 0.0012). CMD in post-PCI target vessels was independently associated with a 3.10-fold increased risk of major adverse cardiovascular events (95% CI: 2.06–4.67) and a 4.66-fold risk of cardiac death or heart failure readmission (95% CI: 3.13–6.93).ConclusionCMD in post-PCI target vessels is prevalent (approximately 40%) and independently associated with a elevated risk of adverse cardiovascular outcomes. Standardized diagnostic criteria and targeted interventions are urgently needed to improve outcomes in this population. Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO CRD42025637496.